Ternary Chalcogenide Nanosheets with Ultrahigh Photothermal Conversion Efficiency for Photoacoustic Theranostics. Issue 16 (10th February 2017) - Zhu, Houjuan; Lai, Zhuangchai; Fang, Yuan; Zhen, Xu; Tan, Chaoliang; Qi, Xiaoying; Ding, Dan; Chen, Peng; Zhang, Hua; Pu, Kanyi
Abstract : 2D materials (TDMs) have been explored for photonic theranostics. To achieve deep‐tissue penetration, near‐infrared (NIR) light is essential for photoacoustic (PA) theranostics. However, because the absorption profiles of existing TDMs are generally featureless with no obvious NIR absorption peaks, their PA signals and therapeutic efficacies are limited. This paper herein reports the synthesis and application of ternary chalcogenide nanosheets (Ta2 NiS5 ‐P) for PA theranostics. In contrast to the current TDMs for such application, Ta2 NiS5 ‐P has a ternary instead of binary composition. This difference brings in the strong and featured NIR for Ta2 NiS5 ‐P. To the best of the knowledge, this is the first example using ternary chalcogenide nanosheets for such application; moreover, the photothermal conversion efficiency of Ta2 NiS5 ‐P is the highest (35%) among all the reported TDMs based on the same calculation method. These advantages allow Ta2 NiS5 ‐P to passively target, effectively delineate, and completely eradicate the tumor of living mice after systemic administration. Abstract : Ternary chalcogenide nanosheets (Ta2 NiS5 ‐P) are developed into photoacoustic theranostic nanoagents for cancer therapy, which have the highest photothermal conversion efficiency (35%) among all the reported 2D materials based on the same calculation method. Owing to its strong and featured absorption in the near‐infrared region, Ta2 NiS5 ‐P enables high‐contrast photoacoustic imaging and effective photothermal therapy of tumor in living mice.